Evaluating outcomes of a clinical pharmacist medication management program in a multidisciplinary practice for outpatient buprenorphine treatment of opioid use disorder. Issue 4 (18th February 2021) - Mattle, Anna G.; Aladeen, Traci; Blondell, Richard D.; Capote, Horacio; Rainka, Michelle
Abstract: Introduction: Treatment with medications such as buprenorphine has been shown to improve outcomes of patients with opioid use disorder (OUD); however, there is still potential to optimize care. Clinical pharmacists may benefit OUD patient treatment by making individualized medication recommendations and enhancing care as part of a multidisciplinary team. This study evaluates a novel outpatient practice model that incorporates pharmacists to manage OUD patients. Methods: A multi‐center retrospective study compared outcomes of a multidisciplinary practice with clinical pharmacists to a physician‐only practice. Primary outcomes were treatment retention and opioid relapse rate. Secondary outcomes included patient engagement with counseling, toxicology results, and buprenorphine nonadherence. Data were collected from 75 patient records from each practice for up to 1 year after starting treatment. In addition, a prospective, observational study was conducted to describe pharmacist interventions at the multidisciplinary practice. Twenty patients were followed for up to 1 year to characterize pharmacist recommendations and assess treatment retention and opioid relapse rates among other secondary measures. Results: In the retrospective study, treatment retention did not differ between practices ( P > .05) but multidisciplinary practice patients experienced fewer opioid relapse months ( P < .05). Similar rates of engagement with counseling ( P = 1) and follow‐up visits with illicit substance use ( P > .05) were observed. More buprenorphine nonadherence was identified at the physician practice ( P < .01). In the prospective study, pharmacist recommendations included buprenorphine regimen changes and the addition of new medications for un/undertreated conditions. Pharmacists provided care coordination, medication counseling, non‐pharmacologic recommendations, and counseling regarding future/alternative treatment options. Conclusion: This study demonstrates the ability of a practice with clinical pharmacists to provide quality care to OUD patients in an outpatient setting. These results have implications for OUD treatment by expanding addiction services in this underserved patient population.